Infecção experimental pelo Encephalitozoon cuniculi em camundongos imunossuprimidos com dexametasona - Lallo, M. A.; dos Santos, M. J.; Bondan, E. F. (Revista de Saúde Publica, 2002)
Objective Microsporidian Encephalitozoon cuniculi has been recognized as an opportunistic pathogen in immunosuppressed individuals, such as AIDS patients. The objective of the study was to develop pharmacologically immunosuppressed animals as a model of the natural occurring E. cuniculi infection.Methods Distint groups of adult Balb-C mice were immunosuppressed with different doses of dexamethasone (Dx, 3 or 5 mg/kg/day, intraperitoneal route - IP) and inoculated with E. cuniculi spores by IP route intraperitoneally. Control groups (inoculated animals but non-immunosuppressed and non-inoculated animals but immunosuppressed) were also used. The spores of E. cuniculi were previously cultivated in MDCK cells. The animals were sacrificed and necropsied at 7, 14, 21, 28 and 35 days post-inoculation. Tissue fragments were collected and processed for light microscopy studies, using Gram-chromotrope and hematoxylin-eosin staining techniques.Results In all immunosupressed and inoculated inoculated immunosuppressed mice,specially in those that received 5 mg/kg/day of dexamethasone, the most prominent necropsy findings were hepatomegaly and splenomegaly. The experimental inoculation resulted in a disseminated non-lethal infection, characterized by granulomatous lesions in several organs (liver lungs, kidneys, gut and brain) but notably in the hepatic tissue. Spores of E. cuniculi were only seen in few animals treated with 5 mg/kg/day of Dx at 35 days post-infection.Conclusions Microsporidiosis in Dx-immunosuppressed mice provides a useful model for studies of the microsporidial infection, resembling that one naturally occurring in immunodeficient individuals with AIDS.
Experimental Encephalitozoon cuniculi infection in dexamethasone-immunosuppressed mice
Keywords: immunocompromised host; encephalitozoon cuniculi; encephalitozoonosis; animal models, disease; mice; inbred Balb C; dexamethasone immunosuppressed